ETNOGRAFI MASYARAKAT MUSLIM MATOTONAN: KEBUDAYAAN MATERIAL, SISTEM MATA PENCAHARIAN, DAN ETNOMEDISIN DI PEDALAMAN SIBERUT - Hernawati Hernawati (Ensiklopedia of Journal, 2026)
The Muslim Matotonan community in the hinterlands of Siberut Island exhibits a unique culture resulting from the acculturation of Islamic values and local Mentawai traditions. This study aims to document the adaptation of their material culture, livelihood systems, and ethnomedicinal practices amidst massive contemporary changes. Utilizing a combination of ethnographic and ethnobotanical methods, field data were gathered through participant observation and in-depth interviews with key informants. The research findings indicate that local material culture has begun to intersect with modern life. In livelihood systems, a shift from traditional hunting to sedentary farming has occurred, along with an increase in agricultural commodity diversification. Meanwhile, in ethnomedicinal aspects, the community aligns the use of local medicinal plants with Islamic principles through natural resource utilization. The study concludes that the Muslim Matotonan community actively engages in dynamic cultural adaptation strategies to maintain the existence of their native identityKeywords: Ethnography; Ethnobotany; Muslim Matotonan; Material Culture; Ethnomedicine